Psychometric Properties of a Newly Online Work Aptitude Test: Faxtor’s Endurance and Speed Test - Whisnu Yudiana; Aryo Bimo Adjie; Nadim Alfan Assa; Anjar Karta Putra (Universitas Ahmad Dahlan, 2023)
The study aimed to investigate the psychometric properties of a new computer-based work aptitude test named Faxtor’s Endurance and Speed Test (F-EAST). Two phases of the study were conducted to examine the reliability of the test and collect the validity evidence based on the relation to other variables. This study used quantitative research with repeated measures designed for 116 participants who participated in two studies (1=63, 54.3% and 2=53, 45.7%).